Regulating Probabilistic Selling of Counterfeits - Gao, Yuetao; Wu, Yue (Management Science, 2023)
Counterfeits are available across many marketplaces. In emerging markets, in particular, consumers often observe a mix of counterfeits and authentic products sold by retailers. It is difficult for some consumers to distinguish between the two types of products. From these consumers’ perspective, the products can be considered as probabilistic goods, and we term retailers’ strategies probabilistic selling of counterfeits. Retailers who sell counterfeits are subject to a penalty by regulation. We develop a game-theoretical model to study this dishonest strategy under regulation. Our model offers the following insights. First, a higher penalty for selling counterfeits can lead to a smaller proportion of authentic products in the market. This finding is driven by a manufacturer’s strategic response: knowing that the penalty becomes higher, the manufacturer has greater incentives to raise the wholesale price of its authentic products. From the retailers’ point of view, this elevated procurement cost can, in turn, encourage them to lower the probability of their products being authentic. Second, manufacturer profit increases with the penalty, whereas retailer profit, consumer surplus, and social welfare do not, in general, exhibit a monotonic relationship with the penalty. This paper was accepted by Dmitri Kuksov, marketing. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4607 .